Faculty Development: A Big Contributor in Medical Education and Clinical Training. - Muhammad Saquib (Journal of Rawalpindi Medical College, 2018)
To grow institutions, competent faculty is required.Growth of competent faculty needs continuous training of faculty in new teaching methods,innovations in medical education and research andvarious faculty development activities. 1 In 1996, there were only 7 institutions offering master level degrees in health professions education in the world. This number increased to 76 in 2010. This explains theimportance of faculty development in institutional growth. 2